Effects of ingested polystyrene microplastics on brine shrimp, Artemia parthenogenetica. (January 2019) - Wang, Ying; Zhang, Dian; Zhang, Mingxing; Mu, Jingli; Ding, Guanghui; Mao, Zheng; Cao, Yifei; Jin, Fei; Cong, Yi; Wang, Lijun; Zhang, Weiwei; Wang, Juying
Abstract: Microplastics are a contaminant of emerging concern which enter the marine environment from a variety of sources. The ingestion and toxic effects of microplastics on marine life, especially for filter feeders, are a cause of concern in view of their ubiquitous nature and their similar size as food sources. To assess the toxic effects of microspheres ingested by brine shrimp larvae, we exposed Artemia parthenogenetica to 10 μm polystyrene microspheres at different concentrations. These concentrations were approximate to the extrapolated marine aquatic environmentally relevant concentrations. The lowest polystyrene concentrations at which ingestion was visualized in A. parthenogenetica were 12 ± 0.57 particles/mL (6.7 ± 0.32 μg/L) and 1.1 ± 0.16 particles/mL (0.61 ± 0.088 μg/L), respectively. There were no significant impacts on the survival, growth or development in A. parthenogenetica occurring over the 14-d exposure across a range of polystyrene nominal concentrations (1–1000 particles/mL or 0.55–550 μg/L). However, abnormal ultrastructures of intestinal epithelial cells were observed upon exposure to polystyrene microspheres, including fewer and disordered microvilli, an increased number of mitochondrion and the appearance of autophagosome. These phenomena could affect nutrition absorption and energy metabolism. Although no major acute or chronic toxicity effects on A. parthenogenetica were observed over 24-h or 14-d exposures, this study provides evidence that the ingestion of polystyrene microplastics at extrapolated environmentally relevant concentrations can be visualized through a microscope to be causing a series of responses in intestinal epithelial cells. Graphical abstract: Image 1 Highlights: The lowest polystyrene concentrations at which ingestion could be visualized were at extrapolated environmentally relevant. No significant impacts of survival, growth and development on A. parthenogenetica occurred. Morphological analysis on digestive tract epithelial cells showed the occurrence of a series of abnormal ultrastructures. Abstract : Although no acute or chronic toxicity effects of ingested microplastics on Artemia were observed, they caused a series of responses in intestinal epithelial cells.